Magnesium-based composite material containing in-situ self-generated core-shell structure particles and preparation method thereof
The core-shell structure particles generated by in-situ self-oxidation and reduction reaction of magnesium-rare earth alloy powder and precursor nanooxide particles, combined with thermal isostatic sintering technology, solve the disadvantage of the interface bonding of ceramic particles and magnesium matrix in magnesium-based composite materials. Problem, improving the high temperature mechanical properties and plasticity of the material, simplifying the preparation process and reducing costs.
Patent Information
- Application Number
- CN202411398582.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-10-09
AI Technical Summary
The differences in crystal structure, electronegativity and bonding methods between ceramic particles and magnesium in magnesium-based composite materials lead to unfavorable interface bonding, reducing material strength, and the huge difference in thermal expansion coefficient and elastic modulus leads to internal stress and affects plasticity.
The core-shell structure particles generated by in-situ self-oxidation reduction reaction of magnesium-rare earth alloy powder and precursor nanooxide particles. The core is pure metal particles and the shell is ceramic particles. It forms dense under high temperature and high pressure through thermal isostatic sintering technology. The core-shell structure particles enhance the strength and plasticity of magnesium-based composites.
The high strength, toughness and elongation performance of magnesium-based composite materials at high temperatures is achieved, the preparation process is simplified, the cost is reduced, and the problems of low wettability and poor bonding of ceramic particles-enhanced magnesium-based composite materials are solved.
Smart Images

Figure CN118895449B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of magnesium-based composites, and in particular to a magnesium-based composite material containing in-situ self-generated core-shell structure particles and a preparation method thereof. Background Art
[0002] In magnesium-based composite materials, ceramic particles are often used as reinforcing particles, but there are differences in crystal structure, electronegativity and bonding between ceramic particles and magnesium. These differences in crystallographic characteristics are not conducive to interfacial bonding and will reduce the strength of the material. In addition, there are huge differences in thermal expansion coefficient and elastic modulus between magnesium and ceramic particles, which makes magnesium-based composite materials produce high internal stress when subjected to temperature or external force loads, resulting in a significant decrease in plasticity.
[0003] In view of this, the present invention is proposed. Summary of the invention
[0004] The object of the present invention is to provide a magnesium-based composite material containing in-situ self-generated core-shell structure particles and a preparation method thereof, so as to solve or improve the above technical problems.
[0005] The present invention can be implemented like this:
[0006] In a first aspect, the present invention provides a magnesium-based composite material containing in-situ self-generated core-shell structure particles, wherein the magnesium-based composite material contains core-shell structure particles generated by an in-situ self-oxidation-reduction reaction of magnesium-rare earth alloy powder and precursor nano-oxide particles; in the core-shell structure particles, the core is a pure metal particle as a reduction product, and the shell is a ceramic particle as an oxidation product;
[0007] The volume percentage of in-situ self-generated core-shell structure particles in magnesium-based composites is 10%~25%;
[0008] The size of the metal particles in the core is 20nm~100nm, and the thickness of the core is 20nm~200nm; the size of the ceramic particles in the shell is 20nm~30nm, and the thickness of the shell is 20nm~50nm.
[0009] The mass of the precursor nano-oxide particles is 1wt%~5wt% of the total mass of the magnesium-rare earth alloy powder and the precursor nano-oxide particles.
[0010] In an optional embodiment, the content of rare earth elements in the magnesium-rare earth alloy powder is 5wt%~10wt%;
[0011] and / or, the rare earth element in the magnesium-rare earth alloy powder includes at least one of Gd, Y, Er, Eu, Nd, Pr, La and Ce;
[0012] And / or, the average particle size of the magnesium-rare earth alloy powder is 80 μm to 100 μm.
[0013] In an optional embodiment, the precursor nano-oxide particles include at least one of TiO2, Al2O3, ZrO2 and Cr2O3;
[0014] And / or, the average particle size of the precursor nano-oxide particles is 30nm~100nm.
[0015] In an optional embodiment, the magnesium-based composite material has at least one of the following characteristics:
[0016] Feature 1: The thickness of the core and the thickness of the shell in the core-shell structure particles are regulated by adjusting the content of rare earth elements and precursor nano-oxide particles;
[0017] Feature 2: The grain size of the magnesium-based composite material does not exceed 3μm;
[0018] Feature 3: The density of magnesium-based composite materials is not less than 98%;
[0019] Feature 4: The tensile strength of the magnesium-based composite material at 300°C is not less than 320MPa;
[0020] Feature 5: The yield strength of the magnesium-based composite material at 300°C is not less than 300MPa;
[0021] Feature 6: The elongation of the magnesium-based composite material at 300°C is not less than 12%.
[0022] In a second aspect, the present invention provides a method for preparing a magnesium-based composite material as described in any of the aforementioned embodiments, comprising the following steps: purging the precursor nano-oxide particles with an inert gas in a closed environment, ball milling with magnesium-rare earth alloy powder, and hot isostatic pressing and sintering.
[0023] In an optional embodiment, no deformation treatment is performed after hot isostatic pressing;
[0024] The deformation process includes hot extrusion, forging and / or rolling.
[0025] In an optional embodiment, the purge time is 5 min to 10 min.
[0026] In an optional embodiment, the ball milling speed is 150 r / min to 180 r / min; the ball-to-material ratio of the ball milling is 20:1 to 25:1 by mass; and the ball milling time is 1.5 h to 3 h.
[0027] In an optional embodiment, the temperature of hot isostatic pressing sintering is 490° C. to 510° C.; the pressure of hot isostatic pressing sintering is 80 MPa to 120 MPa; and the time of hot isostatic pressing sintering is 1.5 h to 2 h.
[0028] In an optional embodiment, oil cooling is performed after heat sealing and static pressure sintering;
[0029] Among them, the cooling rate is 1℃ / min~2℃ / min.
[0030] The beneficial effects of the present invention include:
[0031] In the magnesium-based composite material containing in-situ self-generated core-shell structure particles proposed by the present invention, the core-shell structure particles integrate the properties of the two materials inside and outside through their unique structural characteristics, and complement each other's deficiencies, thereby showing superior performance in enhancing the strength and plasticity of the composite material. In the in-situ self-generated core-shell structure particles, the interior is a self-reduction product metal particle, and the exterior is coated with a self-oxidation product ceramic particle, and both particles are nanometer-sized; the in-situ self-generated core-shell structure particles are co-lattice with the magnesium matrix, have good interface bonding, and the core-shell structure particles can effectively hinder the expansion of cracks and have high deformation storage energy. In addition, the core-shell structure particles can simultaneously play the advantages of metal and ceramic particles and have high high-temperature thermodynamic stability. Therefore, the magnesium-based composite material containing in-situ self-generated core-shell structure particles provided by the present invention can have high strength, toughness, elongation and other properties at high temperatures (such as 300°C).
[0032] The preparation method of the magnesium-based composite material provided by the present invention is simple to operate, has a short preparation process, and is low in cost. It can solve the difficult problems of low wettability, poor bonding, and inconsistent deformation of the interface of the ceramic particle-reinforced magnesium-based composite material, which leads to interface stress concentration. By combining the in-situ reaction with the hot isostatic pressing sintering technology, wherein the hot isostatic pressing sintering uses an inert gas as a pressure transmission medium, the same pressure acts evenly on the surface of the component from all directions, and by applying high temperature and high pressure in a closed container, the processed part is subjected to balanced pressure in all directions, thereby achieving sintering and densification of the product. In addition, by utilizing the high efficiency and high controllability of hot isostatic pressing sintering, the precursor particles can be controlled to react in situ with the surrounding magnesium-rare earth matrix at a relatively low sintering temperature. By diffusing the elements in all directions under pressure, the redox reaction between the rare earth elements and the precursor oxide is promoted, thereby preparing a magnesium-based composite material reinforced with core-shell structure particles. This method does not require subsequent deformation treatments such as hot extrusion, forging, and rolling to obtain a high-density structure, greatly shortening the preparation process and helping to refine the grain size, thereby significantly improving the strength and plasticity of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0034] Figure 1 This is a schematic diagram of the structure of the in-situ self-generated core-shell structure particles prepared in Example 1;
[0035] Figure 2 This is a fracture morphology diagram of the magnesium-based composite material prepared in Example 1;
[0036] Figure 3 This is a longitudinal cross-sectional SEM image of the magnesium-based composite material prepared in Example 1;
[0037] Figure 4 This is a cross-sectional SEM image of the magnesium-based composite material prepared in Example 1;
[0038] Figure 5 This is a cross-sectional SEM image of the magnesium-based composite material prepared in Example 2;
[0039] Figure 6 This is a cross-sectional SEM image of the magnesium-based composite material prepared in Example 3;
[0040] Figure 7 This is a cross-sectional SEM image of the magnesium-based composite material prepared in Comparative Example 1. DETAILED DESCRIPTION
[0041] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0042] The magnesium-based composite material containing in-situ self-generated core-shell structure particles and the preparation method thereof provided by the present invention are specifically described below.
[0043] The inventor proposed that based on the above problems of using ceramic particles as reinforcing particles, if metal particles are used as reinforcing particles, although metal particles have better deformation ability than ceramic particles and are more helpful to improve the plasticity of the composite material, however, metal particles or magnesium matrix are prone to produce brittle metal compounds at the interface, and some metal particles are not soluble in and do not react with the magnesium matrix, resulting in weak interface bonding, which will also affect the strength of the composite material.
[0044] Therefore, the present invention proposes a scheme of in-situ self-oxidation-reduction reaction of magnesium-rare earth alloy powder and precursor nano oxide particles, so that the core-shell structure particles generated by the reaction are coherent with the magnesium matrix, so as to improve the interface bonding and contribute to the effect of load transfer. Moreover, the magnesium-based composite material under this mode is not conducive to the expansion of cracks and has a higher deformation storage energy. In addition, the core-shell structure particles formed by pure metal particles-ceramic particles can simultaneously exert the respective advantages of metal and ceramic particles, have a higher high-temperature thermodynamic stability, and can not only improve the yield strength and tensile strength of the magnesium-based composite material, but also improve the elongation of the magnesium-based composite material.
[0045] The magnesium-based composite material containing in-situ self-generated core-shell structure particles provided by the invention comprises core-shell structure particles generated by in-situ self-oxidation-reduction reaction of magnesium-rare earth alloy powder and precursor nano-oxide particles.
[0046] In the above core-shell structured particles, the core is a pure metal particle as a reduction product, and the shell is a ceramic particle as an oxidation product.
[0047] The volume percentage of the in-situ self-generated core-shell structure particles in the magnesium-based composite material can be 10%-25%, such as 10%-24%, such as 10%, 11%, 12%, 15%, 18%, 21%, 22% or 24%, etc., or other values within the range of 10%-25%.
[0048] If the volume percentage of the in-situ self-generated core-shell structure particles is lower than 10%, it is not conducive to improving the strength of the composite material; if the volume percentage of the in-situ self-generated core-shell structure particles is higher than 25%, it is easy to cause a certain loss of plasticity of the composite material.
[0049] The size of the metal particles in the core may be 20 nm to 100 nm, such as 30 nm to 100 nm, such as 30 nm, 35 nm, 40 nm, 45 nm, 50 nm or 100 nm, etc., or may be other values within the range of 20 nm to 100 nm.
[0050] If the size of the metal particles in the core is less than 20 nm, it is not conducive to the uniform dispersion of the nanoparticles and easily leads to obvious agglomeration; if the size of the metal particles in the core is greater than 100 nm, it is not conducive to controlling the thickness of the shell material generated by the in-situ reaction.
[0051] The thickness of the core may be 20 nm to 200 nm, such as 40 nm to 185 nm, such as 40 nm, 42 nm, 100 nm, 105 nm, 110 nm, 120 nm, 150 nm, 180 nm or 185 nm, or other values within the range of 20 nm to 200 nm.
[0052] The thickness of the core directly affects the magnitude of the interfacial force between the two phases. An appropriate thickness of the core layer can enhance the interaction between the interfaces, thereby improving the overall mechanical properties of the material. Too thick or too thin a core layer may lead to insufficient interfacial force. If the thickness of the core is less than 20nm, the interfacial force is insufficient, affecting the plasticity of the composite material; if the thickness of the core is greater than 200nm, it may lead to poor stress transfer and affect the overall behavior of the material.
[0053] The size of the ceramic particles in the shell may be 20 nm to 30 nm, such as 20 nm to 29 nm, such as 20 nm, 21 nm, 22 nm, 23 nm, 26 nm or 29 nm, etc., or may be other values within the range of 20 nm to 30 nm.
[0054] If the size of the ceramic particles in the shell is less than 20nm, the reinforcing effect on the matrix is weak. This is because small particles may not be able to effectively bear and transfer stress, resulting in no significant improvement in the strength and hardness of the composite material. In addition, small particles may be more likely to separate from the matrix at the interface, thereby affecting the overall stability of the composite material; if the size of the ceramic particles in the shell is greater than 30nm, it may form stress concentration points in the matrix, causing the matrix around the particles to be destroyed first when the material is subjected to external forces, thereby reducing the overall strength and toughness of the composite material. In addition, large particles may also hinder dislocation movement, affect the material's plastic deformation ability, and further reduce the material's ductility and impact resistance.
[0055] The thickness of the shell may be 20 nm to 50 nm, such as 20 nm to 30 nm, such as 20 nm, 21 nm, 22 nm, 23 nm, 24 nm, 28 nm or 30 nm, etc., or other values within the range of 20 nm to 50 nm.
[0056] Appropriate shell thickness is conducive to the uniform transfer of stress in the material, avoiding stress concentration, thereby improving the tensile properties of the material. Similarly, if the shell thickness is less than 20nm, it is easy to cause insufficient interfacial force, which is not conducive to hindering the expansion of cracks at the interface and it is difficult to significantly improve the plasticity of the composite material; if the shell thickness is greater than 50nm, it is not conducive to the uniform transfer of load at the interface, and it is easy to cause stress concentration at the interface to cause premature failure and fracture of the composite material.
[0057] The mass of the precursor nano oxide particles can be 1wt% to 5wt% of the total mass of the magnesium-rare earth alloy powder and the precursor nano oxide particles, such as 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt% or 5wt%, etc., or other values within the range of 1wt% to 5wt%. In some preferred embodiments, the mass of the precursor nano oxide particles can be 2wt% of the total mass of the magnesium-rare earth alloy powder and the precursor nano oxide particles.
[0058] If the mass of the precursor nano-oxide particles is small (such as 0.5wt%), it will not have a good strengthening effect; if the mass of the precursor nano-oxide particles is large (such as 6wt%), it will be unfavorable for the uniform distribution of the particles, and excessive particles will easily agglomerate on the interface, which is not conducive to the strong interface bonding between the particles and the matrix, and the material plasticity is poor.
[0059] In some optional embodiments, the content of rare earth elements in the magnesium-rare earth alloy powder can be 5wt%~10wt%, such as 5wt%, 5.5wt%, 6wt%, 6.5wt%, 7wt%, 7.5wt%, 8wt%, 8.5wt%, 9wt%, 9.5wt% or 10wt%, etc., or other values within the range of 5wt%~10wt%. In some preferred embodiments, the content of rare earth elements can be 7wt%~9wt%; in some more preferred embodiments, the content of rare earth elements can be 8wt%.
[0060] If the content of rare earth elements in the magnesium-rare earth alloy powder is lower than 5wt%, it is not easy to undergo self-oxidation-reduction reaction to form core-shell structure particles, and the high-temperature thermal stability of the composite material is difficult to ensure; if the content of rare earth elements is higher than 10wt%, the price is expensive and is not conducive to industrial production.
[0061] As mentioned above, by limiting the content of rare earth elements and precursor nano-oxides within the above range, on the one hand, it can ensure that a portion of the rare earth elements can completely reduce the nano-oxide particles to form core-shell structure particles with metal inside and ceramic outside, and on the other hand, it can ensure that the remaining rare earth elements can be dissolved into the magnesium alloy matrix to improve plasticity.
[0062] Taking the ceramic particles as TiO2 and the rare earth as Y as an example, if the TiO2 particles are far more than the Y element in the magnesium matrix, the excess nano-TiO2 is easy to agglomerate and difficult to disperse evenly, affecting the uniformity of the composite material's structure, and the deformation ability of the ceramic particles themselves is quite different from that of the matrix magnesium alloy, which will greatly reduce the plasticity of the composite material; if the TiO2 particles are far less than the Y element in the magnesium matrix, only a small amount of TiO2 is reduced to Ti, the Y2O3 layer generated by external self-oxidation is also thinner, the overall mass volume fraction of the core-shell structure particles is small, and the strengthening effect is significantly weakened.
[0063] The rare earth element in the magnesium-rare earth alloy powder may illustratively but not limitatively include at least one of Gd, Y, Er, Eu, Nd, Pr, La, and Ce.
[0064] The average particle size of the magnesium-rare earth alloy powder can be 80 μm to 100 μm, such as 80 μm, 85 μm, 90 μm, 95 μm or 100 μm, etc., or other values within the range of 80 μm to 100 μm. In some preferred embodiments, the average particle size of the magnesium-rare earth alloy powder can be 85 μm to 95 μm. In some more preferred embodiments, the average particle size of the magnesium-rare earth alloy powder is 90 μm.
[0065] If the average particle size of the magnesium-rare earth alloy powder is less than 80μm, the magnesium alloy powder is highly active, and the material is not only easily oxidized during the preparation process, but also poses a safety risk, which is not conducive to industrial production. If the average particle size of the magnesium-rare earth alloy powder is greater than 100μm, it is not conducive to the sintering densification of the composite material, and the path for the internal rare earth elements to diffuse to the surface for self-oxidation-reduction reaction is longer, which is not conducive to the formation of the core-shell structure.
[0066] In some optional embodiments, the precursor nano-oxide particles may illustratively but not limitatively include at least one of TiO2, Al2O3, ZrO2 and Cr2O3.
[0067] The average particle size of the precursor nano oxide particles can be 30nm~100nm, such as 30nm, 35nm, 40nm, 45nm, 50nm, 60nm, 70nm, 80nm, 90nm or 100nm, etc., or other values within the scope of 30nm~100nm. In some preferred embodiments, the average particle size of the precursor nano oxide particles is 40nm~90nm. In some more preferred embodiments, the average particle size of the precursor nano oxide particles is 50nm.
[0068] The smaller the average particle size of the precursor nano oxide particles, the larger the specific surface area of the particles, the more active atoms on the surface, and the easier it is for surface diffusion to proceed. The nano metal powder with an average particle size of 30nm to 100nm adopted in the present invention has a higher activity, is conducive to being evenly distributed on the substrate surface, promotes the self-oxidation reduction reaction of rare earth elements and precursor nano oxides, and contributes to the generation of core-shell structure. If the average particle size of the precursor nano oxide particles exceeds 100nm, it is easy to cause the material activity to decrease, the core diameter of the core-shell structure after reduction is larger, and the gaps between particles are larger, and the reaction in the solid state is not conducive to the formation of a dense composite material.
[0069] In the present invention, the thickness of the core and the thickness of the shell in the core-shell structure particles can be respectively regulated by regulating the contents of the rare earth elements and the precursor nano-oxide particles.
[0070] In some optional embodiments, the grain size of the magnesium-based composite material does not exceed 3 μm, such as 1.4 μm to 2.5 μm, such as 1.4 μm, 1.5 μm, 1.6 μm, 1.8 μm, 1.9 μm, 2.0 μm, 2.2 μm, 2.3 μm, 2.4 μm or 2.5 μm.
[0071] The magnesium-based composite material within this range has fine grains, a large number of grain boundaries, and greater resistance to dislocation movement, which is conducive to enhancing the plastic deformation resistance of the magnesium alloy. In addition, the more grains there are, the more metal plastic deformation can be dispersed inside the grains, and the grain boundaries hinder the expansion of cracks, thereby improving the storage energy of the composite material.
[0072] In some optional embodiments, the density of the magnesium-based composite material is not less than 98%, such as 98.52% to 99.30%, such as 98.52%, 98.61%, 98.62%, 98.84%, 98.92%, 99.21%, 99.03%, 99.11%, 99.21% or 99.30%, etc., and can also be other values within the range of 98.52% to 99.30%.
[0073] In some optional embodiments, the tensile strength of the magnesium-based composite material at 300° C. is not less than 320 MPa, such as 328 MPa to 346 MPa, such as 328 MPa, 330 MPa, 332 MPa, 334 MPa, 339 MPa, 340 MPa, 341 MPa, 342 MPa or 346 MPa, etc., and may also be other values within the range of 328 MPa to 346 MPa.
[0074] In some optional embodiments, the yield strength of the magnesium-based composite material at 300°C is not less than 300 MPa, such as 313 MPa-327 MPa, such as 313 MPa, 316 MPa, 318 MPa, 319 MPa, 320 MPa, 322 MPa or 327 MPa, or may be other values within the range of 313 MPa-327 MPa.
[0075] In some optional embodiments, the elongation of the magnesium-based composite material at 300°C is not less than 12%, such as 13% to 18%, such as 13%, 14%, 15%, 16%, 17% or 18%, etc., and can also be other values within the range of 13% to 18%.
[0076] As mentioned above, in the magnesium-based composite material containing in-situ self-generated core-shell structure particles proposed by the present invention, the core-shell structure particles integrate the properties of the two materials inside and outside through their unique structural characteristics, and complement each other's deficiencies, thereby showing superior performance in enhancing the strength and plasticity of the composite material. In the in-situ self-generated core-shell structure particles, the interior is a self-reduction product metal particle, and the exterior is coated with a self-oxidation product ceramic particle, and both particles are nanometer-sized; the in-situ self-generated core-shell structure particles are co-lattice with the magnesium matrix, have good interface bonding, and the core-shell structure particles can effectively hinder the expansion of cracks and have high deformation storage energy. In addition, the core-shell structure particles can simultaneously play the advantages of metal and ceramic particles and have high high-temperature thermodynamic stability. Therefore, the magnesium-based composite material containing in-situ self-generated core-shell structure particles provided by the present invention can have high strength, toughness, elongation and other properties at high temperatures (such as 300°C).
[0077] Accordingly, the present invention also provides a method for preparing the above-mentioned magnesium-based composite material, comprising the following steps: purging the precursor nano-oxide particles with an inert gas in a closed environment, then ball milling with magnesium-rare earth alloy powder, and hot isostatic pressing and sintering.
[0078] In the present invention, no deformation treatment (including hot extrusion, forging and / or rolling) is required after hot isostatic pressing and sintering, and the magnesium-based composite material can also obtain a higher density, which greatly shortens the preparation process, saves preparation time and cost, and reduces energy consumption.
[0079] In the present invention, the precursor nano-oxide particles are purged with an inert gas (such as argon and / or nitrogen) in a closed environment to remove impurities adsorbed on the surface of the precursor nano-oxide particles, thereby preventing the impurities from adversely affecting the in-situ redox reaction.
[0080] In some optional embodiments, the purge time may be 5 min to 10 min, such as 5 min, 6 min, 7 min, 8 min, 9 min or 10 min, etc., or may be other values within the range of 5 min to 10 min.
[0081] If the purging time is too short, the impurities adsorbed on the surface of the precursor nano-oxide particles cannot be completely removed. By using an inert gas instead of air or other oxygen-containing gas for purging, the precursor nano-oxide particles can be prevented from further oxidation and deterioration or the impurities adsorbed on the surface can be prevented from forming other oxide impurities.
[0082] In some optional embodiments, the ball mill speed can be 150r / min~180r / min, such as 150r / min, 155r / min, 160r / min, 165r / min, 170r / min, 175r / min or 180r / min, or other values within the range of 150r / min~180r / min.
[0083] The ball-to-material ratio of the ball mill can be 20:1 to 25:1 by mass, such as 20:1, 21:1, 22:1, 23:1, 24:1 or 25:1, or other values within the range of 20:1 to 25:1.
[0084] The ball milling time can be 1.5 h to 3 h, such as 1.5 h, 2 h, 2.5 h or 3 h, or other values within the range of 1.5 h to 3 h.
[0085] By ball milling and mixing for a long time in an inert atmosphere, the rare earth elements can be promoted to promote in-situ self-oxidation-reduction reaction at the interface. The rare earth elements can reduce the precursor nano-oxide particles to form core-shell structure particles, so that the precursor nano-oxide particles are evenly coated on the surface of the magnesium-rare earth alloy powder.
[0086] In some optional embodiments, the hot isostatic pressing sintering temperature may be 490°C to 510°C, such as 490°C, 495°C, 500°C, 505°C or 510°C, or other values within the range of 490°C to 510°C.
[0087] When using spark plasma sintering powder, there will be more holes or defects in the sintered blank at a sintering temperature below 490°C, and the material density is poor; when the temperature is higher than 510°C, the magnesium alloy powder reaches the melting point and melts into liquid, which is not conducive to the material's formability.
[0088] The pressure of hot isostatic pressing sintering can be 80 MPa to 120 MPa, such as 80 MPa, 85 MPa, 90 MPa, 95 MPa, 100 MPa, 105 MPa, 110 MPa, 115 MPa or 120 MPa, or other values within the range of 80 MPa to 120 MPa.
[0089] If the sintering pressure is too small, the pores between the powders will be difficult to sinter completely and the material density will not be high; if the sintering pressure is too large, it may cause abnormal growth of the grains in the material and even cause the core-shell structure particles to decompose at high temperatures, thus affecting the performance and stability of the composite material.
[0090] The hot isostatic pressing sintering time may be 1.5 h to 2 h, such as 1.5 h, 1.8 h or 2 h, etc., or may be other values within the range of 1.5 h to 2 h.
[0091] If the sintering time is too long, the grain structure will grow too coarse; if the sintering time is too short, the interface reaction and diffusion between the powder particles will be weak, which is not conducive to material densification.
[0092] As mentioned above, by hot isostatic pressing sintering under closed conditions, under the action of higher pressure, the elements diffuse in all directions, promoting the occurrence of in-situ self-oxidation-reduction reaction at the interface, and in-situ self-reduction can be performed to generate core-shell structured particles, which can significantly hinder the expansion of cracks while giving full play to the respective advantages of the core and shell materials.
[0093] In some optional embodiments, the heat-sealed static pressure sintering is followed by oil cooling, which has a relatively slow cooling rate and can reduce deformation and cracking of the material.
[0094] The cooling rate may be 1°C / min to 2°C / min, such as 1°C / min, 1.5°C / min or 2°C / min, or other values within the range of 1°C / min to 2°C / min.
[0095] As mentioned above, the preparation method provided by the present invention is simple to operate, has a short preparation process, and is low in cost. It can solve the problem of low wettability, poor bonding, and inconsistent deformation of ceramic particle-reinforced magnesium-based composite materials, which leads to interface stress concentration. By combining the in-situ reaction with the hot isostatic pressing sintering technology, in which the hot isostatic pressing sintering uses an inert gas (such as nitrogen and argon) as a pressure transmission medium, the same pressure acts evenly on the surface of the component from all directions, and by applying high temperature and high pressure in a closed container, the processed part is subjected to balanced pressure in all directions, thereby achieving sintering and densification of the product. In addition, by utilizing the high efficiency and high controllability of hot isostatic pressing sintering, the precursor particles can be controlled to react in situ with the surrounding magnesium-rare earth matrix at a relatively low sintering temperature, and the rare earth elements and the precursor oxide are promoted to undergo redox reactions by diffusing the elements in all directions under the action of pressure, thereby preparing a magnesium-based composite material reinforced with core-shell structure particles. This method does not require subsequent deformation treatments such as hot extrusion, forging, and rolling to obtain a high-density structure, greatly shortening the preparation process and helping to refine the grain size, thereby significantly improving the strength and plasticity of the composite material.
[0096] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0097] Example 1
[0098] This embodiment provides a magnesium-based composite material containing in-situ self-generated core-shell structure particles, and the preparation method thereof includes:
[0099] S1: TiO2 powder with an average particle size of 50 nm was purged with argon gas in a closed environment for 10 min.
[0100] S2: The argon-purged TiO2 and magnesium-rare earth alloy powder with an average particle size of 90 μm (Mg-8Y powder containing 8 wt % Y) were mixed in a mass ratio of 1:99 and then subjected to high-energy ball milling to obtain a composite powder.
[0101] Among them, in terms of mass ratio, the ball-to-material ratio is 25:1; the ball milling speed is 150r / min; and the ball milling time is 2h.
[0102] S3: hot isostatic pressing the composite powder, and then cooling the powder to room temperature by oil cooling to obtain a magnesium-based composite material.
[0103] The hot isostatic pressing sintering temperature was 500°C, the hot isostatic pressing sintering time was 2h, and the hot isostatic pressing sintering pressure was 100MPa. Finally, a magnesium-based composite material containing in-situ self-generated core-shell structure particles (expressed as Y2O3@Ti) was obtained. The cooling rate of oil cooling was 1.5°C / min.
[0104] The magnesium-based composite material containing in-situ self-generated core-shell structure particles prepared in this embodiment, wherein the core of the core-shell structure is pure Ti particles and the outer shell is Y2O3 particles, and both particles are nanometer-level.
[0105] Example 2
[0106] The difference between this embodiment and embodiment 1 is that TiO2 and Mg-8Y powder are mixed in a mass ratio of 2:98.
[0107] Example 3
[0108] The difference between this embodiment and embodiment 1 is that TiO2 and Mg-8Y powder are mixed in a mass ratio of 3:97.
[0109] Example 4
[0110] The difference between this embodiment and embodiment 1 is that TiO2 and Mg-8Y powder are mixed in a mass ratio of 5:95.
[0111] Example 5
[0112] The difference between this embodiment and embodiment 1 is that the content of rare earth elements in the magnesium-rare earth alloy powder can be 7wt%, the average particle size of the magnesium-rare earth alloy powder can be 85μm, and the average particle size of the precursor nano-oxide particles is 40nm.
[0113] Example 6
[0114] The difference between this embodiment and embodiment 1 is that the content of rare earth elements in the magnesium-rare earth alloy powder can be 9wt%, the average particle size of the magnesium-rare earth alloy powder can be 95μm, and the average particle size of the precursor nano-oxide particles is 90nm.
[0115] Example 7
[0116] The difference between this embodiment and embodiment 1 is that the content of rare earth elements in the magnesium-rare earth alloy powder can be 5wt%, the average particle size of the magnesium-rare earth alloy powder can be 80μm, and the average particle size of the precursor nano-oxide particles is 30nm.
[0117] Example 8
[0118] The difference between this embodiment and embodiment 1 is that the content of rare earth elements in the magnesium-rare earth alloy powder can be 10wt%, the average particle size of the magnesium-rare earth alloy powder can be 100μm, and the average particle size of the precursor nano-oxide particles is 100nm.
[0119] Example 9
[0120] This embodiment provides a magnesium-based composite material containing in-situ self-generated core-shell structure particles, and the preparation method thereof includes:
[0121] S1: Al2O3 powder with an average particle size of 30 nm was purged with argon gas for 5 min in a closed environment.
[0122] S2: Al2O3 purged with argon gas and magnesium-rare earth alloy powder with an average particle size of 80 μm (Mg-5Ce powder containing 5 wt% Ce) were mixed in a mass ratio of 1:99 and then subjected to high-energy ball milling to obtain a composite powder.
[0123] Among them, in terms of mass ratio, the ball-to-material ratio is 20:1; the ball milling speed is 160r / min; and the ball milling time is 3h.
[0124] S3: hot isostatic pressing the composite powder, and then cooling the powder to room temperature by oil cooling to obtain a magnesium-based composite material.
[0125] The hot isostatic pressing sintering temperature is 490°C, the hot isostatic pressing sintering time is 1.8h, and the hot isostatic pressing sintering pressure is 80MPa. Finally, a magnesium-based composite material containing in-situ self-generated core-shell structure particles is obtained. The cooling rate of oil cooling is 1°C / min.
[0126] The magnesium-based composite material containing in-situ self-generated core-shell structure particles prepared in this embodiment, wherein the core-shell structure has pure Al particles inside and Ce2O3 particles outside, and both particles are nanometer-level.
[0127] Example 10
[0128] This embodiment provides a magnesium-based composite material containing in-situ self-generated core-shell structure particles, and the preparation method thereof includes:
[0129] S1: Cr2O3 powder with an average particle size of 40 nm was purged with argon gas in a closed environment for 8 min.
[0130] S2: Cr2O3 purged with argon gas was mixed with magnesium-rare earth alloy powder with an average particle size of 100 μm (Mg-10Gd powder containing 10 wt % of Gd) at a mass ratio of 1:99 and then subjected to high-energy ball milling to obtain a composite powder.
[0131] Among them, in terms of mass ratio, the ball-to-material ratio is 22:1; the ball milling speed is 180r / min; and the ball milling time is 1.5h.
[0132] S3: hot isostatic pressing the composite powder, and then cooling the powder to room temperature by oil cooling to obtain a magnesium-based composite material.
[0133] The hot isostatic pressing sintering temperature is 510°C, the hot isostatic pressing sintering time is 1.5h, and the hot isostatic pressing sintering pressure is 120MPa. Finally, a magnesium-based composite material containing in-situ self-generated core-shell structure particles is obtained. The cooling rate of oil cooling is 2°C / min.
[0134] The magnesium-based composite material containing in-situ self-generated core-shell structure particles prepared in this embodiment, wherein the core-shell structure has pure Cr particles inside and Gd2O3 particles outside, and both particles are nanometer-level.
[0135] Comparative Example 1
[0136] The difference between this comparative example and Example 1 is that no precursor nano-oxide particles are added, and pure Mg8Y alloy is used.
[0137] Comparative Example 2
[0138] The difference between this comparative example and Example 1 is that the mass of the precursor nano-oxide particles is 0.5wt% of the total mass of the magnesium-rare earth alloy powder and the precursor nano-oxide particles.
[0139] Comparative Example 3
[0140] The difference between this comparative example and Example 1 is that the mass of the precursor nano-oxide particles is 6wt% of the total mass of the magnesium-rare earth alloy powder and the precursor nano-oxide particles.
[0141] Comparative Example 4
[0142] The difference between this comparative example and Example 1 is that the content of rare earth elements in the magnesium-rare earth alloy powder is 2 wt %.
[0143] Comparative Example 5
[0144] The difference between this comparative example and Example 1 is that the content of rare earth elements in the magnesium-rare earth alloy powder is 12 wt %.
[0145] Comparative Example 6
[0146] The difference between this comparative example and Example 1 is that the average particle size of the magnesium-rare earth alloy powder is 60 μm.
[0147] Comparative Example 7
[0148] The difference between this comparative example and Example 1 is that the average particle size of the magnesium-rare earth alloy powder is 120 μm.
[0149] Comparative Example 8
[0150] The difference between this comparative example and Example 1 is that the average particle size of the precursor nano-oxide particles is 20 nm.
[0151] Comparative Example 9
[0152] The difference between this comparative example and Example 1 is that the average particle size of the precursor nano-oxide particles is 120 nm.
[0153] Comparative Example 10
[0154] The difference between this comparative example and Example 1 is that during the preparation process, S1 is not performed, and the precursor nano-oxide particles and the magnesium-rare earth alloy powder are directly subjected to S2, and then to S3.
[0155] Comparative Example 11
[0156] The difference between this comparative example and Example 1 is that the S1 process is carried out in an air atmosphere.
[0157] Comparative Example 12
[0158] The difference between this comparative example and Example 1 is that the ball milling time in S2 is 1 h.
[0159] Comparative Example 13
[0160] The difference between this comparative example and Example 1 is that in S3, the hot isostatic pressing sintering temperature is 480°C.
[0161] Comparative Example 14
[0162] The difference between this comparative example and Example 1 is that in S3, the hot isostatic pressing sintering temperature is 520°C.
[0163] Comparative Example 15
[0164] The difference between this comparative example and Example 1 is that in S3, the hot isostatic pressing sintering pressure is 150 MPa.
[0165] Comparative Example 16
[0166] The difference between this comparative example and Example 1 is that in S3, the hot isostatic pressing sintering time is 4 hours.
[0167] Comparative Example 17
[0168] The difference between this comparative example and Example 1 is that in S3, the temperature is lowered by air cooling.
[0169] Test example
[0170] ①. The morphology of the magnesium-based composite materials prepared in the above-mentioned embodiments and comparative examples was tested. In addition, the core-shell structure particles in each magnesium-based composite material were characterized by transmission fine structure. The results are as follows: Figures 1 to 7 And as shown in Table 1.
[0171] Table 1 Characterization
[0172]
[0173] It can be seen from Table 1 that the volume percentage of the in-situ self-generated core-shell structure particles in the magnesium-based composite materials prepared in the embodiments of the present invention is in the range of 10% to 25%, and the size of the metal particles in the core is in the range of 20nm to 100nm, and the thickness of the core is 20nm to 200nm; the size of the ceramic particles in the shell is in the range of 20nm to 30nm, and the thickness of the shell is in the range of 20nm to 50nm.
[0174] Depend on Figure 1 It can be seen that the magnesium-based composite material prepared in Example 1 contains nano-scale core-shell structure particles. Figure 2 It can be seen that the Y2O3 layer in the fracture morphology can significantly hinder the propagation of cracks, which helps to increase the storage energy of the composite material and improve the plasticity of the composite material.
[0175] In addition, taking the magnesium-based composite materials prepared in Examples 1 to 3 and Comparative Example 1 as examples, the longitudinal section SEM images and the cross-sectional SEM images of the magnesium-based composite materials prepared in Example 1 are respectively as follows: Figure 3 and Figure 4 The cross-sectional SEM image of the magnesium-based composite material prepared in Example 2 is shown in FIG. Figure 5 The cross-sectional SEM image of the magnesium-based composite material prepared in Example 3 is shown in FIG. Figure 6 As shown, the cross-sectional SEM image of the magnesium-based composite material prepared in Comparative Example 1 is as follows Figure 7 shown.
[0176] ② The mechanical properties and density of the magnesium-based composite materials prepared in the above embodiments and comparative examples were tested, and the results are shown in Table 2.
[0177] Among them, the yield strength, tensile strength and elongation at 300°C are tested in accordance with GB / T228.2-2015. The density is tested in accordance with GB3850-83.
[0178] Table 2 Mechanical properties and density test results at 300℃
[0179]
[0180] It can be seen from Table 2 that the magnesium-based composite material prepared in the embodiment of the present invention has higher yield strength, tensile strength, elongation and density than the magnesium-based composite material prepared in the comparative example.
[0181] In summary, the magnesium-based composite material containing in-situ self-generated core-shell structure particles provided by the present invention has fine grains, and the core (metal reduction product) and shell (ceramic oxidation product) are generated in-situ inside, which can effectively hinder the expansion of cracks and improve the mechanical properties and deformation storage energy of the composite material at high temperature. At the same time, the preparation method of the magnesium-based composite material is simple to operate, the preparation process is short, the cost is low, and it can be industrialized.
[0182] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A magnesium-based composite material containing in-situ self-generated core-shell structure particles, characterized in that: The magnesium-based composite material contains core-shell structure particles generated by in-situ self-oxidation-reduction reaction of magnesium-rare earth alloy powder and precursor nano-oxide particles; in the core-shell structure particles, the core is a pure metal particle as a reduction product, and the shell is a ceramic particle as an oxidation product; The volume percentage of the in-situ self-generated core-shell structure particles in the magnesium-based composite material is 10% to 25%; The size of the metal particles in the core is 20nm-100nm, and the thickness of the core is 20nm-200nm; the size of the ceramic particles in the shell is 20nm-30nm, and the thickness of the shell is 20nm-50nm; the mass of the precursor nano-oxide particles is 1wt%-5wt% of the total mass of the magnesium-rare earth alloy powder and the precursor nano-oxide particles; The content of rare earth elements in the magnesium-rare earth alloy powder is 5wt% to 10wt%; the rare earth elements in the magnesium-rare earth alloy powder are selected from at least one of Gd, Y, Er, Eu, Nd, Pr, La and Ce; The precursor nano oxide particles are selected from at least one of TiO2, Al2O3, ZrO2 and Cr2O3.
2. The magnesium-based composite material according to claim 1, characterized in that: The average particle size of the magnesium-rare earth alloy powder is 80 μm to 100 μm.
3. The magnesium-based composite material according to claim 1, characterized in that: The average particle size of the precursor nano-oxide particles is 30nm-100nm.
4. The magnesium-based composite material according to any one of claims 1 to 3, characterized in that: The magnesium-based composite material has at least one of the following characteristics: Feature 1: The thickness of the core and the thickness of the shell in the core-shell structure particles are respectively regulated by regulating the content of the rare earth element and the precursor nano-oxide particles; Feature 2: The grain size of the magnesium-based composite material does not exceed 3 μm; Feature 3: The density of the magnesium-based composite material is not less than 98%; Feature 4: The tensile strength of the magnesium-based composite material at 300°C is not less than 320 MPa; Feature 5: The yield strength of the magnesium-based composite material at 300°C is not less than 300 MPa; Feature 6: The elongation of the magnesium-based composite material at 300°C is not less than 12%.
5. A method for preparing a magnesium-based composite material according to any one of claims 1 to 4, characterized in that: The following steps are involved: The precursor nano-oxide particles are purged with an inert gas in a closed environment, and then ball-milled with magnesium-rare earth alloy powder and sintered by hot isostatic pressing.
6. The preparation method according to claim 5, characterized in that: No deformation treatment is performed after hot isostatic pressing; The deformation process includes hot extrusion, forging and / or rolling.
7. The preparation method according to claim 5 or 6, characterized in that: The purge time is 5min~10min.
8. The preparation method according to claim 5 or 6, characterized in that: The ball milling speed is 150r / min~180r / min; the ball-to-material ratio of the ball milling is 20:1 to 25:1 by mass; and the ball milling time is 1.5h~3h.
9. The preparation method according to claim 5 or 6, characterized in that: The temperature of hot isostatic pressing sintering is 490℃~510℃; the pressure of hot isostatic pressing sintering is 80MPa~120MPa; the time of hot isostatic pressing sintering is 1.5h~2h.
10. The preparation method according to claim 5 or 6, characterized in that: Oil cooling after heat sealing and static pressure sintering; Among them, the cooling rate is 1℃ / min~2℃ / min.